Koalisi Partai Politik untuk Demokrasi: Membangun Demokrasi Kebangsaan dalam Nuansa Pluralisme - Yusa Djuyandi (Humaniora, 2011)
In building altogether goodness in democracy and nationality frame, party coalition in presidential and regional head election is not something impossible to be done and even for some people it is needed. Though in Indonesia, political parties could be generated into religion and nationalist parties, religion fundamental in political party in Indonesia has not succeed. The existence of party coalition with different platform or ideology in presidential election on 2004 and 2009, also the execution of regional head election showed that concern towards fundamental existence has no eligible reason. Due to the plurality of Indonesia, cooperation among political parties in building the nations should leave several dichotomies; which will only bring this nation to continuous ideological disintegration and conflict. This also will affect to the nation’s ideal and purpose.